The Relationship Between Body Image and Imaginary Audience Among Adolescent Girls in Makassar - Arsi, Nurul Maulida; Ridfah, Ahmad; Pratiwi, Novi Yanti (Polteknik Ilmu Pemasyarakatan, 2025)
Adolescent girls undergo a developmental stage marked by significant physical and social changes that influence how they perceive themselves, particularly in relation to body image. During this period, they often feel as though they are constantly being observed and judged by others, a psychological phenomenon known as the imaginary audience. These perceptions can shape either a positive or negative body image. This study aimed to examine the relationship between body image and the imaginary audience among adolescent girls in Makassar City. This study aims to determine the relationship between body image and imaginary audience in adolescent girls in Makassar City. The subjects in this study were adolescent girls in Makassar City aged 15 to 17 years. The sample technique used was quota sampling. Body Image was measured using the Multidimensional Body-Self Relations Questionnaire-Appearance Scales (MBSRQ-AS), imaginary audience was measured using the New Imaginary Audience Scale (NIAS). Hypothesis testing using Spearman Rank correlation analysis. The results of the analysis obtained are p = 0.000 <0.005 or there is a very significant relationship between body image and imaginary audience in adolescent girls in Makassar City. The correlation coefficient of body image variable with imaginary audience is 0.476 or classified as moderate. These findings suggest that the more positive the body image, the greater the tendency to experience an imaginary audience. The implications highlight the importance to helping adolescent girls develop a positive body image so they can become more confident and less concerned about how others judge them.